FLIGHT SAFETY AND IMPROVEMENT OF MECHANISM AND SECURITY - Філик, Наталія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the article is dedicated to the analysis of the current state of aviation safety and prospects for improvement. It has been proven that flight safety is a basic category in air travel on the background of growing local conflicts. Methods of research: the study is carried out using conventional methods of scientific cognition, such as: analytical, comparative-legal, semantic-cognitive, systemic, statistical and others. The methodology of this study is based on a systematic approach by which a particular object is viewed as a multidimensional phenomenon consisting of various elements, the relationships between which form a relatively stable safety flight structure. Results: it is stated that «crisis response mechanisms need to be improved», namely that recommendations should be developed for clear and clear actions for the relevant aviation authorities, diplomatic services and officials, which will prevent manipulation and political statements of emotional nature. We believe that Ukraine should initiate the establishment of an appropriate international aviation regulator to ensure the safety of civil aviation in high-risk countries and to establish new rules and standards that meet the challenges of the times and enable the airspace in those countries to be closed quickly and without bureaucracy, which are in a high-risk area because of the threat of terrorist or military attacks. Discussion: finding ways to improve the functional areas of preventing aviation accidents and improving flight safety. Separately, it should be noted that the international commu nity should improve the rules of aviation security legislation and establish clear criteria and conditions for the responsibility of the country for not ensuring the safety of airspace over their country.